Fuzzy certificateless signature. Issue 16 (9th August 2016) - Wang, Liangliang; Lai, Junzuo; Xiong, Hu; Chen, Kefei; Long, Yu
Abstract: According to the inspirations from history, we introduce a new cryptography primitive called fuzzy certificateless signature, which not only eliminates the key escrow problem inherently existed in fuzzy identity‐based signature but also possesses the error tolerance property of fuzzy identity‐based signature that allows for a set of attributes ω to verify a signature produced with a private key for an identity ω ′ if and only if the distance between the two identities ω and ω ′ is within a certain threshold. In this paper, the concept of fuzzy certificateless signature is first proposed, and then, the syntax and security model of fuzzy certificateless signature are formally defined. In the next step, so far, the first concrete fuzzy certificateless signature scheme is proposed, which may be practicably implemented in biometric identification. In addition, a formal security proof is provided, so as to demonstrate that in the random oracle model, our newly proposed scheme is existentially unforgeable against Types I and II chosen message attacks formalized in the security model under the computational Diffie–Hellman assumption. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : In this paper, the concept of fuzzy certificateless signature is proposed and then the syntax and security model of fuzzy certificateless signature are formally defined. In the next step, so far, the first concrete fuzzy certificateless signature scheme is proposed, which may be practicably implemented in biometric identification. In addition, a formal security proof is provided, so as to demonstrate that in the random oracle model, our newly proposed scheme is existentially unforgeable under the computational Diffie Hellman assumption.